Bayesian analysis of multimessenger M-R data with interpolated hybrid EoS - Ayriyan, Alexander (2021)
We introduce a family of equations of state (EoS)for hybrid neutron star (NS) matter that is obtained by atwo-zone parabolic interpolation between a soft hadronicEoS at low densities and a set of stiff quark matter EoSat high densities within a finite region of chemical potentialsμH < μ < μQ. Fixing the hadronic EoS as the APRone and choosing the color-superconducting, nonlocal NJLmodel with two free parameters for the quark phase, we performBayesian analyses with this two-parameter family ofhybrid EoS. Using three different sets of observational constraintsthat include the mass of PSR J0740+6620, the tidaldeformability for GW170817, and the mass-radius relationfor PSR J0030+0451 from NICER as obligatory (set 1), whileset 2 uses the possible upper limit on themaximummass fromGW170817 as an additional constraint and set 3 instead ofthe possibility that the lighter object in the asymmetric binarymerger GW190814 is a neutron star. We confirm that in anycase, the quark matter phase has to be color superconductingwith the dimensionless diquark coupling approximately fulfillingthe Fierz relation ηD = 0.75 and the most probablesolutions exhibiting a proportionality between ηD and ηV , thecoupling of the repulsive vector interaction that is requiredfor a sufficiently largemaximummass.We used theBayesiananalysis to investigate with the method of fictitious measureaments the consequences of anticipating different radii for themassive 2 M PSR J0740+6220 for the most likely equationof state. With the actual outcome of the NICER radius measurementon PSR J0740+6220 we could conclude that for themost likely hybrid star EoS would not support a maximummass as large as 2.5 M so that the event GW190814 was abinary black hole merger.